Effects of periodontal therapy on C-reactive protein and HDL in serum of subjects with periodontitis - Anne Carolina Eleutério Leite (Brazilian Journal of Cardiovascular Surgery, 2014)
Objective: To investigate the effects of nonsurgical periodontal therapy on levels of high-sensitivity C-reactive protein in the sera and its association with body mass index and high density lipoprotein in subjects with severe periodontitis. Methods: Sera from 28 subjects (mean age: 34.36±6.24; 32% men) with severe periodontitis and 27 healthy controls (mean age: 33.18±6.42; 33% men) were collected prior to periodontal therapy. Blood samples were obtained from 23 subjects who completed therapy (9-12 months). Oral and systemic parameters such as the number of blood cells, glucose examination, lipid profile, and high-sensitivity C-reactive protein levels accessed by high-sensitivity immunonephelometry assay, were included. Results: Before therapy, in the periodontitis group, the ratio of subjects with high-sensitivity C-reactive protein <0.3 mg/dL was statistically lower than in the control group (P<0.0216). After therapy, the ratio of subjects with high-sensitivity C-reactive protein <0.3 mg/dL was significantly higher (65.22%) (P<0.0339). The mean value for body mass index was statistically lower in subjects with high-sensitivity C-reactive protein <0.3 mg/dL (24.63±4.19), compared with those with high-sensitivity C-reactive protein >0.3 mg/dL (28.91±6.03) (P<0.0411). High density lipoprotein presented a mean value statistically higher after therapy (P<0.0027). Conclusion: In systemically healthy subjects with periodontitis, periodontal therapy was associated with decreased levels of circulating high-sensitivity C-reactive protein and increase of high density lipoprotein in serum. The clinical trial was registered at http://www.clinicaltrials.gov.br/, No. RBR-24T799.